Antihypertensive Treatment Improves Microvascular Rarefaction and Reactivity in Low‐Risk Hypertensive Individuals. (November 2013) - Kaiser, Sérgio E.; Sanjuliani, Antonio F.; Estato, Vanessa; Gomes, Marilia B.; Tibiriçá, Eduardo
Abstract: Objective: To test whether long‐term antihypertensive treatment with metoprolol succinate (a β1 ‐adrenoceptor blocker) or olmesartan medoxomil (an angiotensin II AT1 ‐receptor blocker) reverses microvascular dysfunction in hypertensive patients. Methods: This study included 44 hypertensive outpatients and 20 age and sex‐matched healthy controls. We used skin capillaroscopy to measure capillary density and recruitment at rest and during PORH. Endothelium‐dependent vasodilation of skin microcirculation was evaluated with a LDPM system in combination with ACh iontophoresis, PORH, and LTH. Results: Pretreatment capillary density in hypertensive patients was significantly reduced compared with controls (71.3 ± 1.5 vs. 80.6 ± 1.8 cap/mm 2 ; p < 0.001), as was PORH (71.7 ± 1.5 vs. 79.5 ± 2.6 cap/mm 2 ; p < 0.05). After treatment for six months, capillary density increased to 75.4 ± 1.1 cap/mm 2 ( p < 0.01) at rest and 76.8 ± 1.1 cap/mm 2 during PORH. During LTH, CVC in perfusion units (PU)/mmHg was similar in patients (1.71 [1.31–2.12]) and controls (1.60 [1.12–1.91]) and increased significantly (1.82 [1.30–2.20]) after treatment. Maximal CVC during PORH was reduced in hypertensive patients (0.30 [0.22–0.39]) compared to controls (0.39 [0.31–0.49], p < 0.001) and increased (0.41 [0.29–0.51], p < 0.001) after treatment. Conclusions: Capillary rarefaction and microvascular endothelial dysfunction in hypertensive patients responded favorably to long‐term pharmacological treatment.